EVALUASI POLA SEBARAN SPASIAL DAN KUALITAS PELAYANAN TERHADAP EFEKTIVITAS SAMSAT KELILING DI KABUPATEN KENDAL - Adriyanto, Riyan Eka; Hariyanto, Hariyanto (Geo-Image, 2019)
Mobile Samsat was created to provide services by ball picking system to remote areas far from central Samsat. Mobile Samsat services in Kendal Regency include Boja District, Sukorejo District, Kaliwungu District, Weleri District, Gemuh District, Cepiring District, and Kendal City. Problems related to the loss of regional income from the motor vehicle tax sector occur in Kendal Regency. this certainly reduces the ability of regions to carry out development both from the economic and infrastructure sectors. The purpose of this study are: (1) Knowing the spatial distribution pattern of mobile Samsat in Kendal Regency; (2) Knowing the quality of mobile Samsat services in Kendal Regency; and (3) Knowing the effectiveness of mobile Samsat services in Kendal Regency. Location of the study is Kendal Regency covering 7 locations of mobile Samsat services. The analysis techniques in this study are: (1) Nearest neighbour analysis; (2) Analysis of the closest distance and opportunity; and (3) Descriptive quantitative analysis. The results of the study show that: (1) The spatial distribution pattern of the mobile Samsat has a random pattern; (2) The quality of service for the mobile Samsat includes good service; and (3) The effectiveness of the mobile Samsat service are still far from the target.